NFATc3 and VIP in Idiopathic Pulmonary Fibrosis and Chronic Obstructive Pulmonary Disease. - Anthony M Szema; Edward Forsyth; Benjamin Ying; Sayyed A Hamidi; John J Chen; Sonya Hwang; Jonathan C Li; Debra Sabatini Dwyer; Juan M Ramiro-Diaz; Wieslawa Giermakowska; Laura V Gonzalez Bosc (PLoS ONE, 2017)
Idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD) are both debilitating lung diseases which can lead to hypoxemia and pulmonary hypertension (PH). Nuclear Factor of Activated T-cells (NFAT) is a transcription factor implicated in the etiology of vascular remodeling in hypoxic PH. We have previously shown that mice lacking the ability to generate Vasoactive Intestinal Peptide (VIP) develop spontaneous PH, pulmonary arterial remodeling and lung inflammation. Inhibition of NFAT attenuated PH in these mice suggesting a connection between NFAT and VIP. To test the hypotheses that: 1) VIP inhibits NFAT isoform c3 (NFATc3) activity in pulmonary vascular smooth muscle cells; 2) lung NFATc3 activation is associated with disease severity in IPF and COPD patients, and 3) VIP and NFATc3 expression correlate in lung tissue from IPF and COPD patients. NFAT activity was determined in isolated pulmonary arteries from NFAT-luciferase reporter mice. The % of nuclei with NFAT nuclear accumulation was determined in primary human pulmonary artery smooth muscle cell (PASMC) cultures; in lung airway epithelia and smooth muscle and pulmonary endothelia and smooth muscle from IPF and COPD patients; and in PASMC from mouse lung sections by fluorescence microscopy. Both NFAT and VIP mRNA levels were measured in lungs from IPF and COPD patients. Empirical strategies applied to test hypotheses regarding VIP, NFATc3 expression and activity, and disease type and severity. This study shows a significant negative correlation between NFAT isoform c3 protein expression levels in PASMC, activity of NFATc3 in pulmonary endothelial cells, expression and activity of NFATc3 in bronchial epithelial cells and lung function in IPF patients, supporting the concept that NFATc3 is activated in the early stages of IPF. We further show that there is a significant positive correlation between NFATc3 mRNA expression and VIP RNA expression only in lungs from IPF patients. In addition, we found that VIP inhibits NFAT nuclear translocation in primary human pulmonary artery smooth muscle cells (PASMC). Early activation of NFATc3 in IPF patients may contribute to disease progression and the increase in VIP expression could be a protective compensatory mechanism.